2022
DOI: 10.1021/acscentsci.1c01578
|View full text |Cite
|
Sign up to set email alerts
|

Precise CO2 Reduction for Bilayer Graphene

Abstract: It is of great significance to explore unique and diverse chemical pathways to convert CO 2 into high-value-added products. Bilayer graphene (BLG), with a tunable twist angle and band structure, holds tremendous promise in both fundamental physics and next-generation high-performance devices. However, the π-conjugation and precise two-atom thickness are hindering the selective pathway, through an uncontrolled CO 2 reduction and perplexing growth mechanism. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…1g ). Note that the original references are also listed in Supplementary Table 1 with more details 9 , 10 , 17 , 21 , 22 , 32 52 . The CO 2 -assisted strategy also exhibits excellent scalability and compatibility with the growth of large-area graphene on Cu foils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1g ). Note that the original references are also listed in Supplementary Table 1 with more details 9 , 10 , 17 , 21 , 22 , 32 52 . The CO 2 -assisted strategy also exhibits excellent scalability and compatibility with the growth of large-area graphene on Cu foils.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon species can either diffuse from the edge of the MLG domains to be consumed in the nucleation and growth of second layers 17 , 18 or diffuse across the Cu bulk to supply the growth of the second layer on the other side of the Cu foil 19 , 20 . However, the reported bilayer coverage of graphene on Cu is still less than 95% 21 , and several hours are required for the growth 22 , 23 . This is because the second-layer graphene usually nucleates underneath the first-layer graphene, resulting in the difficulty in the continuous supply of active carbon species 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the work, Wei et al utilized the CO 2 derived graphene by demonstrating its remarkable ability to keep its performance over time, showing consistent energy storage capacity of 130 mA•h•g −1 even after undergoing 1000 cycles at a current density of 1.0 A•g −1 to be used for lithium-ion battery [149]. In another work, Gong et al showed that bilayer graphene exhibits significant promise for next-generation electrical and twistronics devices due to its configurable band-gap and favorable properties [179]. Despite the numerous advancements in this field, a comprehensive review of the processing methods for CO 2 -based nanostructures and their applications in energy-related contexts has yet to be provided in the literature.…”
Section: Applications Of Co 2 Derived Graphene Materialsmentioning
confidence: 99%
“…176,[178][179][180] Dye-sensitize solar cells and perovskite solar cells Photovoltaic energy conversion[154,181,182] Environmental remediation Sustainable practices, eco-friendly technologies[183][184][185] …”
mentioning
confidence: 99%